RPV‐modified epirubicin and dioscin co‐delivery liposomes suppress non‐small cell lung cancer growth by limiting nutrition supply. Issue 2 (18th January 2020) - Kong, Liang; Cai, Fu‐yi; Yao, Xue‐min; Jing, Ming; Fu, Min; Liu, Jing‐jing; He, Si‐yu; Zhang, Lu; Liu, Xin‐ze; Ju, Rui‐jun; Li, Xue‐tao
Abstract: Chemotherapy for non‐small cell lung cancer (NSCLC) is far from satisfactory, mainly due to poor targeting of antitumor drugs and self‐adaptations of the tumors. Angiogenesis, vasculogenic mimicry (VM) channels, migration, and invasion are the main ways for tumors to obtain nutrition. Herein, RPV‐modified epirubicin and dioscin co‐delivery liposomes were successfully prepared. These liposomes showed ideal physicochemical properties, enhanced tumor targeting and accumulation in tumor sites, and inhibited VM channel formation, tumor angiogenesis, migration and invasion. The liposomes also downregulated VM‐related and angiogenesis‐related proteins in vitro. Furthermore, when tested in vivo, the targeted co‐delivery liposomes increased selective accumulation of drugs in tumor sites and showed extended stability in blood circulation. In conclusion, RPV‐modified epirubicin and dioscin co‐delivery liposomes showed strong antitumor efficacy in vivo and could thus be considered a promising strategy for NSCLC treatment. Abstract : Targeted epirubicin and dioscin co‐delivery liposomes modified with RPV increased cellular uptake and accumulation in the A549 cells. The RPV‐modified epirubicin and dioscin co‐delivery liposomes enhanced anti‐tumor efficacy in vitro and in vivo. The RPV‐modified epirubicin and dioscin co‐delivery liposomes inhibited NSCLC migration and invasion by limiting tumor angiogenesis and vasculogenic mimicry formation.